TKO hiring! : ten knockout strategies for recruiting, interviewing, and hiring great people - Anderson, Dave, 1961- (Hoboken, N.J. : John Wiley & Sons, 2008)
Practical business guides that pull no punches. Dave Anderson's TKO series presents no-nonsense, down-in-the-trenches management strategies that work in the real world of business. Each of the three informative books in this series offers easy-to-
Round one : Understand the cost of hiring recklessly -- Round two : Become a proactive recruiter -- Round three : Create a potent interview structure -- Round four : Ask tough interview questions -- Round five : Effectively check references -- Round six : How to use predictive testing hiring profiles -- Round seven : How to get new hires off to a great start -- Round eight : How to retain eagles once you find them -- Round nine : Differentiate your employees for development and retention -- Round ten : Knockout summary for follow- through.
Includes bibliographical references (page 119) and index.
Print version record.
John Wiley and Sons
Keywords: Employees -- Recruiting; Employment interviewing; Employee selection; Personnel Selection; Personnel -- Recrutement; Entretiens d'embauche.; Personnel; BUSINESS & ECONOMICS -- Workplace Culture; BUSINESS & ECONOMICS -- Human Resources & Personnel Management; Employee selection; Employees -- Recruiting; Employment interviewing